„Uchwycić kopię” czy podjąć własną aktywność myślową? O nauczaniu porównywania różnicowego i ilorazowego w szkole - Elżbieta Mrożek (Problemy Wczesnej Edukacji)
The additive and multiplicative compare word problems are specifically difficult. The sources of these difficulties may lie in the nature of these tasks and the wrong teaching. In this article I have presented a proposal to amend the existing methodology of teaching to solve compare word problems by introducing a curriculum based on the constructivist approach. This change consists in the fact that at the beginning of schooling the pupils get familiar with the compare word problems on manipulated specific objects and simple numbers. Additive compare problem should be derived from the pupils’ activities associated with one-to-one correspondence assigned on the occasion of comparing the sets of numbers. In the idea of the constructivist approach to the multiplicative compare problem, it derives from the pupils’ activities, referring to measuring length by repeatedly applying a device to a measured object. Traditional methods used in the teaching of compare word problems (which is connected with characteristic phrases in tasks and verbal communication) are not very effective and develop only schematic thinking (in the negative sense of the word).